ISLAMIC BANKING PERFORMANCE MEASUREMENT: A CONCEPTUAL REVIEW OF TWO DECADES - Rosmanidar, Elyanti; Hadi, Abu Azam Al; Ahsan, Muhamad (International Journal of Islamic Banking and Finance Research, 2021)
This article aims to provide an overview of the development of research on the measurement of Islamic banking performance over the past 20 years from 89 selected papers with Scopus-indexed journals ranked Q4 to Q1 or accredited with Sinta 2 to Sinta 1. This study used a qual-quantitative meta-analysis approach using the Mendeley citation application. The distribution of the topic and the depth of research in paper samples based on keywords in publications were analyzed using the VOSviewer application. The results of the analysis showed that the research trend of Islamic banking performance in reputable journals is increasing in recent years. Most of the studies performed in the last two decades have focused on the practice and corporate governance of Islamic banks and comparisons between Islamic and conventional banks based on financial performance ratios and aspect of maqasid al-Shariah; Only a few studies that discuss efficiency, social performance on Islamic banks, regulation, intellectual capital and stability of the financial performance of Islamic banks were found. The further discussion is an empirical exposure without theoretical exploration or analysis which is supposed to become the direction of banking research in the future. JEL Classification Codes: G21, L25, P17, P47.